Recruitment and Organizational Performance of Association of Sisterhoods of Kenya - Julius, Joyce Karambu; Njeje, Doreen; Dr. Allan Kihara , Allan (Human Resource and Leadership Journal, 2024)
Purpose: This study investigated the influence of the recruitment process on the performance of the Association of Sisterhoods of Kenya. The study was aimed at examining the influence of recruitment methods, selection process, employment interview, placement, and induction. The study analyzed Contingency, Human Capital, Resource-based, and Person-Organization Theories. The study adopted a survey research design subjecting all A.O.S.K. employees. Methodology: The study used descriptive methods for qualitative and quantitative. The data were collected using a structured questionnaire and an interview scheduled. The study carried out census sampling where 60 employees participated and purposive sampling for the advisory board where 3 members were interviewed. The data collected were analyzed using descriptive design for the qualitative data which included opinions, and experiences. The qualitative data collected were analyzed using SPSS software. The data were presented using frequency tables, percentages, and charts. Findings: The findings showed that recruitment ensures that qualified professionals are harnessed to meet the rising needs. It was determined from the study analysis that there was a correlation coefficient of 0.906 and determination coefficients of 0.821, indicating a strong association between recruitment methods, selection process, employment interview, placement and induction and organizational performance. The study concluded that the recruitment method of employee referrals by the existing employee and word of mouth took precedence in recruitment in A.O.S.K. The study also concluded that application screening and background checks are positively and significantly related. The study also concluded that in the employment interview, the employees are examined on their past job experience working under pressure. The recruitment process enhanced A.O.S.K.'s efforts to get the right employees, skilled and knowledgeable in their work, improving performance. The study further concluded that employee placement and induction have been taken seriously by the office of HR where the new employees meet the Human Resource Officer on the first day for orientation and training. Unique contributions to theory, practice and policy: The study recommended that the management of A.O.S.K. clear recruitment procedures to be followed by all the applicants. The study also recommended minimizing employee referrals in the employment process to avoid a scenario where all employees in the organization are related to each other. To enable organization continuity, knowledge management be promoted.